-6x+10+7x=4+x+6

Simple and best practice solution for -6x+10+7x=4+x+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6x+10+7x=4+x+6 equation:


Simplifying
-6x + 10 + 7x = 4 + x + 6

Reorder the terms:
10 + -6x + 7x = 4 + x + 6

Combine like terms: -6x + 7x = 1x
10 + 1x = 4 + x + 6

Reorder the terms:
10 + 1x = 4 + 6 + x

Combine like terms: 4 + 6 = 10
10 + 1x = 10 + x

Add '-10' to each side of the equation.
10 + -10 + 1x = 10 + -10 + x

Combine like terms: 10 + -10 = 0
0 + 1x = 10 + -10 + x
1x = 10 + -10 + x

Combine like terms: 10 + -10 = 0
1x = 0 + x
1x = x

Solving
1x = x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
1x + -1x = x + -1x

Combine like terms: 1x + -1x = 0
0 = x + -1x

Combine like terms: x + -1x = 0
0 = 0

Simplifying
0 = 0

The solution to this equation could not be determined.

See similar equations:

| 3d=9+6d | | 3ab-2-4ab= | | 20k^2-38+12=0 | | 5x+13-8x=17-17x+14x-4 | | 5m+1=10+4m | | -9+4r=1+2r | | -1(4n+2)=-2(2n-1) | | 11x-89=7x+19 | | 200m-5600=0 | | 5x+30=3x-10 | | 0=5x^2-12x+4 | | -3f=-f+6 | | 5(3r-1)=55 | | 8n-2n+7=29 | | 4n^2+21n-18= | | 3n+2=-19 | | 10x-1=4x+23 | | 2.5x=x+100*2.5 | | 0.5m=10 | | 324+x^2=900 | | 9v=-10+8v | | z=xl | | 4(x^2)-32=84 | | 2.5x=x+100 | | 6-4n+3n=20-25 | | -7(4x+3)=-21 | | 9+3+2a-2=a+4 | | x^2-32=21 | | 8x-55=5x-7 | | 2(w-58)=(w+497)-58 | | 8c+d=12d-5 | | 18+13+n=-9 |

Equations solver categories